De finska och svenska nämndemannasystemen - En komparativ och framåtblickande analys - Eriksson,David (2023)
The element of lay judges is present in both the Swedish and Finnish legal systems. Together with professional judges, lay judges assume different roles in the two countries constituting the courts. A constantly relevant question in Sweden is whether the system should be reformed or perhaps even abolished. In Sweden, municipalities and provinces select the lay judges. For some, this poses a concern for the politicization of the courts where the rule of law might be placed in jeopardy. Other voices raise concerns that lay judges in general, because of a lack of legal knowledge and inability to filter out legally irrelevant circumstances, are less able to carry out their work in a satisfactory manner than professional judges. Furthermore, the paper establishes the rules regulating the Swedish and Finnish lay judges. More specifically, the role of the lay judges in the legal system, how lay judges are appointed, and which people are eligible as lay judges form the object of investigation in the paper. A comparative analysis was conducted where the Swedish and Finnish systems are set against each other, and similarities and differences are pinpointed. For example, the systems are much alike each other in terms of how lay judges are appointed, and the eligibility of lay judges. The study also revealed differences between the Swedish and Finnish law. In Sweden for example, lay judges appear in appellate courts and more types of cases than they do in Finland. Arguments for and against the current Swedish regulations are presented to shine a light on the potential strengths and weaknesses of the system. Finally, a discussion de lege ferenda follows where suggestions for reforms are put forward. These suggestions are supported by the arguments made in the paper and take in some part inspiration from the Finnish system.
Keywords: processrätt; komparativ rätt